1977
DOI: 10.1139/e77-081
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and alteration of selected units of Mid-Atlantic Ridge basalts sampled from sites 332 and 335, DSDP

Abstract: Closely spaced samples spanning 'flow units' at suh-bottom depths of 500 and 590 m in the drill hole at site 332B and a pillow at depth of 460 m, site 335. as well as a few individual samples at various depths in these holes and in the hole at site332A. were studied with a view to determining compositional changes effected by suhmarine alteration. The rocks are predominanlly plagioclase-olivine phyric tholeiitic hasalts. with the exception ofthe lower unit of 332B. which is a picrite formed by the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…This concentric zoning of the pillow lavas has already been described in samples from Leg 37 (Baragar et al, 1977), and observed by the authors in samples from Leg 46 (Lofgren, 1971). It is a primary structure indicating fast cooling conditions.…”
Section: Mineralogy Of Alteration In Basalts From Site 417supporting
confidence: 78%
See 1 more Smart Citation
“…This concentric zoning of the pillow lavas has already been described in samples from Leg 37 (Baragar et al, 1977), and observed by the authors in samples from Leg 46 (Lofgren, 1971). It is a primary structure indicating fast cooling conditions.…”
Section: Mineralogy Of Alteration In Basalts From Site 417supporting
confidence: 78%
“…The varioles are generally centered around a microlite or microphenocryst of plagioclase (An 50 to 75), which is surrounded by a thin rim of fibrous, brown, and anisotropic minerals; after Baragar et al (1977), these tiny rims would be made of plagioclase and pyroxene. In the spherulitic zone (SZ), 1 cm thick, the varioles join together, forming a polygonal net.…”
Section: Mineralogy Of Alteration In Basalts From Site 417mentioning
confidence: 99%
“…A study of pillows from the seafloor weathering zone and low-temperature zone of hole CY1/1A shows that pillow interiors are either unaltered or have the same trends in element mobility as pillow rims but to a lesser degree [Baragar et al, 1991]. Similar trends of element mobility have also been documented for rim-core pairs of pillows altered at low-temperatures [Baragar et al, 1977] and at greenschist facies conditions [Hump hris and Thompson, 1978]. Thus qualitative compositional trends are discussed in following section for each alteration zone in hole CY1/1A.…”
Section: Chemical Effects Of Alterationmentioning
confidence: 83%
“…Available data on the chemical composition of such secondary products were obtained from Baragar et al(1977), Banks (1972), Melson and Thompson (1973), Bass (1976), Seyfried et al (1976), Scott and Swanson (1976), Scheidegger and Stakes (1977), and the present study. The analyzed samples in these papers are believed to be representative of the compositions of alteration products found in oceanic crust, both in regard to age (0 to 110 m.y.B.P.)…”
Section: Evidence For Evolutionary Changes In the Composition Of Secomentioning
confidence: 99%